FROM SERVICE EXCELLENCE TO CUSTOMER LOYALTY: INVESTIGATING THE MEDIATING ROLE OF SATISFACTION AT PT DANDANOMA MAHA AGUNG - Hidayat, Salas; Sulistiyawan, Edy; Rahman, Moch. Munir (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research examines how service quality impacts customer satisfaction and repurchase intention at PT Dandanoma Maha Agung. It utilizes path analysis to test its hypotheses. The findings indicate a positive and significant relationship between service quality and customer satisfaction. Effective service quality can fulfill customer expectations, create positive experiences, and reduce the likelihood of dissatisfaction, thereby enhancing customer satisfaction. Furthermore, service quality also positively influences repurchase intention, suggesting that higher service quality leads to increased customer intention to repurchase products or services. Moreover, the study reveals that customer satisfaction positively affects repurchase intention, indicating that customer satisfaction serves as a mediator between service quality and repurchase intention. These results suggest the importance for PT Dandanoma Maha Agung to consistently improve its service quality to bolster customer satisfaction and repurchase intention, consequently achieving a competitive edge and greater customer loyalty.